MATLAB/simulink cable joint modelling using S-Parameter for defect assessment - Kuan T.M.; Sulaiman S.; Ariffin A.M.; Radhi M.A.R. (Institute of Advanced Scientific Research, Inc., 2023)
This study presents the simulation results of time domain reflectometry (TDR) cable system modelled using MATLAB/Simulink for defect assessment. The cable is modelled with single jointing where scattering parameters (S-parameters) is used to represent the cable joint. A series of simulations are conducted and results are then verified with the experimental results. This paper discusses the validation of the simulation results which are found to be consistent with the experimental results. Thus, the cable model is valid and can be used for assessing defects along a cable. 2018, Institute of Advanced Scientific Research, Inc. All rights reserved.